2011
DOI: 10.1021/es103595g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dispersion on Adsorption of Atrazine by Aqueous Suspensions of Fullerenes

Abstract: With the widespread application of fullerenes, it is critical to assess their environmental behaviors and their impacts on the transport and bioavailability of organic contaminants. The effects of fullerene particle size, chemistry of the solution, and natural organic matter on the adsorption of atrazine by aqueous dispersions of fullerenes (C60) were investigated in this work. The results showed that the Polanyi-Manes model could fit the adsorption isotherms well. Smaller sizes of fullerene particles led to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
2
35
1
Order By: Relevance
“…In addition, atrazine might be dominantly adsorbed in its molecular form onto the negatively charged photocatalyst surfaces at the given pH (Supplementary Figure S13c). 45 Furthermore, its photocatalytic activity remained high after five cycles (Supplementary Figure S15), suggesting its good photocatalytic stability. The observed partial activity loss might be due to incomplete photocatalyst collection, organic surface deactivation and decreased adsorption capacity.…”
Section: Adsorption-promoted Degradation Of Low-concentration Refractmentioning
confidence: 99%
“…In addition, atrazine might be dominantly adsorbed in its molecular form onto the negatively charged photocatalyst surfaces at the given pH (Supplementary Figure S13c). 45 Furthermore, its photocatalytic activity remained high after five cycles (Supplementary Figure S15), suggesting its good photocatalytic stability. The observed partial activity loss might be due to incomplete photocatalyst collection, organic surface deactivation and decreased adsorption capacity.…”
Section: Adsorption-promoted Degradation Of Low-concentration Refractmentioning
confidence: 99%
“…In view of these facts, it was considered worthwhile to develop fast, effective, economic and reproducible method for the subtraction of atrazine from water. The literature shows some adsorption methods for the removal of atrazine (Gai et al 2011;Zhang et al 2011;Chaparadza and Hossenlopp 2012;Báez et al 2013;Silva et al 2013;Zhao et al 2013;Yola et al 2014;Gupta et al 2015). It was observed that some methods work at extreme pHs, which are not suitable to work under natural water conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hyung et al [12] revealed that dissolved organic matter (DOM) could bind with carbon nanotubes in aquatic systems through p-p interaction, and the steric and electrostatic stabilization offered by DOM greatly enhanced their stability and transport in water [13]. Shi et al [14] reported that the presence of HA helped inhibit the formation of fullerene aggregates and increased its dispersion in solution, consequently atrazine adsorption on fullerenes was enhanced. Additionally, HA could also coat on the surface of titanium dioxide and ferroferric oxide nanoparticles, making removal of heavy metals from water more effective [15,16].…”
Section: Introductionmentioning
confidence: 99%